Дезире: роман / Анна-Мария Зелинко - Зелинко Анна-Мария (КУбК, 1993)
Экземпляры: аб. (1993) / Инвентарный номер: 36726 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: З-49 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44